Post-Communism and the South African Communist Party. Issue 4 (4th July 2019) - Lodge, Tom
Abstract : In what ways does the trajectory of the South African Communist Party correspond with general features of post-communist politics? This paper will show how the party remains far from being reconstituted as a post-communist formation. The party's leadership remains inspired by Leninist precepts and its own historic strategic perspectives, and draws purpose from its proximity to power. But it struggles to maintain a vanguard function in a political economy in which the industrial working class has weakened and its own mass membership, recruited from unemployed rural youngsters, is motivated by office-seeking rather than solidarity.